Vertical Angulation Alteration Tolerance in the Periapical Radiograph of Maxillary Incisor (An in vitro Study) - Antolis, Maureen; Priaminiarti, Menik; Kiswanjaya, Bramma (UI Scholars Hub, 2014)
The prevalence of vertical distortion in the periapical radiograph of the anterior maxillary teeth is quite significant and cingulum is commonly used as the reference of vertical distortion in anterior radiograph. Objective: To evaluate the limit of vertical angulation error that still can be tolerated. Methods: Periapical radiograph with vertical angle 0° was obtained from 30 maxillary incisors as reference, then the vertical angulation was changed into -10°, +10°, -15°, +15°, -20° and +20°. Long axis of the teeth was adjusted parallel to the film. Tooth length and cingulum width with vertical angulation alteration was measured and compared to the actual length. All of the measurement was tested using T test. Results: There were no significant differences between all the measurements of tooth length with the alteration in vertical angulation (p>0.05), whereas cingulum width had a significant difference at +15° and -10°, p